Discussing differences between groups: The content of intergroup encounters and motivation for social change among members of advantaged groups. (17th September 2017) - Vezzali, Loris; Andrighetto, Luca; Capozza, Dora; Di Bernardo, Gian Antonio; Saguy, Tamar
Abstract: Recent research highlighted that intergroup contact can inadvertently undermine social change. However, relatively little work had linked experiences of contact to motivation for social change among advantaged groups. We develop the hypothesis that the association between amount of intergroup contact and motivation for social change depends on the content of the encounter. Specifically, intergroup contact that prioritizes differences between groups (over commonalities) can predict greater motivation for social change among members of advantaged groups. Our findings reveal, consistent with the literature on preferences for the content of contact, that an intergroup interaction that is focused on differences predicts greater motivation for social change, but only if such interaction is part of repeated positive contact experiences. We discuss theoretical and practical implications of findings.